THE EFFECT OF WORK ENVIRONMENT AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE AT UPTD PUSKESMAS TELUK JAMBE - Hesti Nur Sapitri; Budi Rismaadi; Neni Sumarni (Jurnal Scientia, 2023)
Efforts to improve the quality of human resources of companies or organizations need to be carried out well, directed, and planned, so that companies or organizations can compete fairly with other companies or organizations, Given that in the future competition between companies will be tighter . Human resources that are able to compete with competitors or with business partners are only companies that have quality human resources. The purpose of this study is to determine the influence of the work environment and work discipline on the work performance of employees at the Telukjambe Health Center UPTD. The analysis technique used is multiple regression analysis through the help of SPSS software version 25. The population of this study was 42 employees and all of them were used as research samples with a sampling method, namely saturated sampling. Questionnaire data collection and tested with validity and reliability tests. The results showed that the work environment and work discipline simultaneously had a significant effect on employee work performance. The work environment has a positive and significant effect on employee work performance. Work discipline has a positive and significant effect on employee work performance.